Equivalent Input Disturbance-Based Control Design for Three Phase Dual-Stage Grid-Tied Photovoltaic System Considering Dead Time Effect - Liu, Fang; Fan, Zhen; Liu, Qianyi; Zou, Runmin (Frontiers in Energy Research, 2021)
Grid-tied inverter is the prominent component of three-phase dual-stage photovoltaic (PV) grid-tied power generation system. However, the disturbances caused by dead time effect will pose the reduction of grid-tied current quality, even cause the imbalance of inverter itself or other circuit devices. In this paper, a current control strategy is proposed to damp dead time effect for three-phase dual-stage PV grid-tied inverter system, and its design, stability analysis and implementation are carried out. Firstly, the inverter model is modified by regarding the dq reference frame coupling terms, uncertainties external and internal disturbances as an unknown lumped disturbance. Then a current control scheme based on compensation of equivalent input disturbance (EID) is introduced, and it estimates and compensates the unknown lumped disturbance, which effectively realizes the inverter model decoupling and comprehensive disturbance rejection. Finally, simulation results demonstrate the effectiveness and superiority of the proposed current controller.